Accelerating skin barrier repair using novel bioactive magnesium-doped nanofibers of non-mulberry silk fibroin during wound healing. (January 2022) - Gupta, Sharda; Dutta, Pallab; Acharya, Veena; Prasad, Pushpa; Roy, Amit; Bit, Arindam
Novel magnesium doped non-mulberry silk fibroin nanofibers with ability to enhance skin barrier function were successfully fabricated using electrospinning technique for wound healing applications. Magnesium nanoparticles incorporated in the electrospun nanofibers releases Mg 2+ ions at the site of implementation. The effect of Mg 2+ is of considerable concern in wound healing due to its skin barrier repair ability and its role in blood coagulation. The physicochemical characterization of the scaffold was investigated by determining the morphology and secondary structure confirmation. The effects of Mg 2+ ions in silk fibroin microenvironment have been evaluated using SEM, XRD, and FTIR to confirm the incorporation of magnesium in the film. The aim of this study is to see the effect of doped Mg on the structural, physical, and biological properties of non-mulberry silk fibroin (NSF) film. The magnesium doped nanofibrous film exhibited enhanced mechanical property, satisfactory blood clotting ability, and good in vitro degradability. This silk fibroin-based film mimicking extracellular matrix for skin regeneration were constructed using electrospinning technique. The wound healing efficiency of prepared nanofibers were evaluated in full-thickness wound models of rat. The Mg doped silk fibroin film exhibited faster wound healing activity (14 days) among all experimental group. The study indicates the potential of magnesium-doped silk /PVA film as skin substitute film.